Upaya Meningkatkan Disiplin Belajar Melalui Layanan Konseling Kelompok Teknik Shaping Pada Siswa Di SMPN 3 Tanggul - Nurul Qomariah; Fakhruddin Mutakin; Arifin Nur Budiono (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2026)
This study aims to determine the improvement of learning discipline through shaping techniques in students at SMPN 3 Tanggul. This study is a guidance and counseling action research. The subjects of the study were all class VIII at SMPN 3 Tanggul totaling 156 students, with 5 students selected by purposive sampling as samples. The data collection method was carried out using a questionnaire. The results showed that 75% had succeeded in achieving the success indicator of the sample experiencing an increase in learning discipline. This finding states that group counseling services using shaping techniques can effectively improve the learning discipline of students at SMPN 3 Tanggul. This study suggests that similar programs be implemented in other schools to improve student learning discipline and to support the optimization of learning in schools. Thus it can be concluded that group counseling using shaping techniques can improve student learning discipline.